Study On Fashion Retail Design In Malaysia: Case Study Gucci, Pavilion, Kuala Lumpur - Mohd Jain Noordin, Mohd Azri (2017)
The emerging of modern retail formats in Malaysia has caused a challenge for existing retailers in competition. Therefore the retailers need to look for ways to deliver better consumer shopping value to increase consumer purchase intention. Past studies found significant relationship between store designs and customer behavior. The store design elements reinforce the retail environment by providing the consumers in experiences around the brand identity which contributed to the store choices and sales. However, only few literatures and researches regarding store design were done in Malaysia especially in fashion retail context.